QTL MAPPING FOR SALINITY TOLERANCE AT SEEDLING STAGE IN RICE - Islam, M. R.; Hassan, L.; Salam, M. A.; Collard, B. C. Y.; Singh, R. K.; Gregorio, G. B. (Emirates Journal of Food and Agriculture, 2011)
Salinity tolerance in rice is a quantitative trait. Rice is sensitive at seedling and reproductive stages; however, the tolerance at seedling stage is crucial for better crop establishment in the field. In the present study, we report the detection of QTLs for salinity tolerance at the seedling stage identified in a F2 breeding population derived from the cross between BRRI dhan40, a moderately tolerant female parent with IR61920-3B-22-2-1 (NSIC Rc106), a highly tolerant male parent. Out of total 300 F2 segregating plants, 93 plants with extreme phenotype for salinity stress response, i.e. tolerant and sensitive, were used for selective genotyping based on of visual seedling stage salt tolerance symptom. A total of 260 SSR and two EST markers evenly spread throughout the whole rice genome at 5 Mb intervals were used for parental polymorphism survey. The 90 polymorphic makers were used for QTL mapping for salinity tolerance at seedling stage. QTL analysis using single marker, interval mapping and composite interval mapping detected three major QTLs on chromosome 1, 8 and 10 with phenotypic variances (R2 ) of 12.50, 29.0 and 20.20%, respectively. The position of QTL on chromosome 1 was flanked by RM8094 and RM3412 marker which is in the same region as a previously identified major QTL designated as SalTol. However, two other QTLs with relatively large effects were flanked by RM25 and RM210 on chromosome 8, and RM25092 and RM25519 on chromosome 10, and appear to be novel QTLs. The markers flanking these QTLs should be useful for molecular marker assisted breeding for salinity tolerance.